From molecules to minds – an integrative framework for living in space - Ip-Jewell, Susan; Badhan, Raj K.; Jewell, Emmy; Sonawane, Surabhi; Srenivasan, Madhumitha (Frontiers in Space Technologies, 2026)
As humanity transitions from episodic exploration to sustained habitation beyond low Earth orbit, the long-term viability of human life in space has become a critical scientific challenge. Survival in extraterrestrial environments requires more than engineering solutions; it demands an integrative approach that addresses molecular stability, physiological regulation, psychological adaptation, and ethical governance. This perspective proposes a unified framework that combines space medicine, multi-omics science, behavioral health, and agentic artificial intelligence to meet the complex demands of long-duration missions. Human heterogeneity, sex-specific physiology, epigenetic plasticity, and the operational boundaries of AI are examined alongside the distinction between adult astronaut adaptation and the unresolved biological risks of multi-generational colonization. By situating technological advancement within a human-centered, ethically governed paradigm, this framework offers a structured roadmap for a sustainable human presence beyond Earth.